Problems of the study of musical traditions of the SouthKazakhstan region (Eurasian Journal of Philology Science and Education, 2016)
In D. Abzhalelova’s article «Problems of the study of musical traditions of the South-Kazakhstan region» gives a brief overview of musicological literature devoted to the study of regional musical traditions in Kazakhstan. The author notes that folklore and oral-professional traditions of an-kuyizhyr of South Kazakhstan region remain poorly understood and reveals the essence of the main issues raised in the thesis: 1) the collection and systematization of musical material in the region, 2) the demonstration of the originality of the song and the epic tradition of the region through the individual styles of the carriers of these traditions, 3) the relationship of South-Kazakh epic tradition with Syr region (Syrdarya) and song tradition with Zhetysu region (through the history of the tribe Dulat as the most numerous in South Kazakhstan).
Keywords: folklore; an art an-kuyi-zhyr (song; instrumental; epic creativity); regional traditions; Shezhire (annals of Kazakh tribes).